Business Student Satisfaction: The Role of Academic and Non-Academic Services in Higher Education Institutions - Gurung, Santosh Kumar; Chapagain, Ramkrishna; Thapa, Kabita (Journal of Business and Management, 2023)
Background: Scholarly literature widely acknowledges the significance of academic and non-academic services in determining student satisfaction in higher education institutions. However, the opinion of students in determining various aspects of academic and non-academic services has not been considered, especially in developing nations.Objectives: This study aims to examine business students’ satisfaction with academic and non-academic services.Methods: 255 business students were purposively selected for this descriptive quantitative study. The reason for adopting purposive sampling in this study is that different people hold different and essential views about the issue and, therefore, must be included in the sample. Using the Higher Education Performance (HedPERFormance) measurement instrument, a 19-item structured survey was developed for self-administration. The data were analyzed using SPSS 21.0 and AMOS 22.0 versions. The variables determining students' satisfaction levels with academic and non-academic services were examined using descriptive statistics. Confirmatory factor analysis and structural equation modelling were used to demonstrate the interrelationship of the three constructs and validate the hypothesis.Results: The study revealed a significant positive relationship between student satisfaction and academic and non-academic services. However, the study results demonstrated a greater significance of academic services for students in higher education institutions.Conclusion: The findings concluded that student satisfaction extends beyond academic services, encompassing nonacademic or administrative services. These aspects directly influence how students perceive and assess the educational institution. This indicates that the satisfaction students derive from their educational experience is not solely reliant on academic factors but is equally shaped by the quality of administrative services, contributing significantly to their overall evaluation of the institution.